PENGARUH PERSEPSI REMUNERASI PEGAWAI, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PERBENDAHARAAN NEGARA (KPPN) PERCONTOHAN SERANG PROVINSI BANTEN - Yeni Widyastuti (Universitas Sultan Ageng Tirtayasa, 2010)
This research maintain to analyze The Influence of Employee’s Remuneration Perception, Work Motivation and Work Discipline to The Employee Performance in The State Treasury Services Office (Kantor Pelayanan Perbendaharaan Negara/KPPN Percontohan) Serang, Banten Province Therefore, in order to strengthening all this variable factors to the employee’s performance, the organization need to more recognize and honouring the employee’s work achievements, career opportunies and also make tranparency and accountability between structural and fungsional employee’s system to reduce the distorsion and unfairness of this remuneration system. About discipline, the punishment had to attended for create the money follows function system in The State Treasury Services Office.